2014
DOI: 10.1103/physrevlett.113.235701
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation at the Contact Line Observed on Nanotextured Surfaces

Abstract: It has been conjectured that roughness plays a role in surface nucleation, the tendency for freezing to begin preferentially at the liquid-gas interface. Using high speed imaging, we sought evidence for freezing at the contact line on catalyst substrates with imposed characteristic length scales (texture). Length scales consistent with the critical nucleus size and with δ∼τ/σ, where τ is a relevant line tension and σ is the surface tension, range from nanometers to micrometers. It is found that nanoscale textu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 43 publications
5
65
0
Order By: Relevance
“…A specific dependence on the INP for the enhancement of contact freezing relative to immersion freezing is in accordance with Gurganus et al (2014), who observed an increased efficiency for nucleation at the three-phase contact line in the case of nanoscale but not for microscale textures. In most experiments of contact freezing inside out, the position of the particle with respect to the droplet is fixed by the design of the experiment Fornea et al, 2009;Gurganus et al, 2014). Whether a particle adheres to the surface or becomes totally immersed in a droplet depends on the wetting of the particle with water.…”
Section: Kaolinitesupporting
confidence: 65%
See 2 more Smart Citations
“…A specific dependence on the INP for the enhancement of contact freezing relative to immersion freezing is in accordance with Gurganus et al (2014), who observed an increased efficiency for nucleation at the three-phase contact line in the case of nanoscale but not for microscale textures. In most experiments of contact freezing inside out, the position of the particle with respect to the droplet is fixed by the design of the experiment Fornea et al, 2009;Gurganus et al, 2014). Whether a particle adheres to the surface or becomes totally immersed in a droplet depends on the wetting of the particle with water.…”
Section: Kaolinitesupporting
confidence: 65%
“…Contact freezing (CF) in the original sense is understood as the process in which freezing of a supercooled droplet results from the collision with an aerosol particle (Ladino Moreno et al, 2013;Vali, 1985). This view of collisional contact freezing has been complemented by Durant and Shaw (2005), who found a higher ice nucleation temperature compared with the immersion mode, when an INP was in contact with the waterair interface of a droplet, from either the inside or the outside Gurganus et al, 2014;Fornea et al, 2009;Murray et al, 2012;Shaw et al, 2005). In the following, we refer to a contact nucleation process as adhesion freezing when the position of the INP on the water surface enhances the ice nucleation efficiency compared with immersion freezing and discriminate it from collisional contact freezing, which assumes an enhancement due to the collision of the particle with the droplet.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This view of collisional contact freezing has been complemented by Durant and Shaw (2005), who found higher ice nucleation temperatures compared with the immersion mode when an ice nucleus was in contact with the water-air interface of a droplet, from either the inside or the outside Gurganus et al, 2014;Fornea et al, 2009;Murray et al, 2012;Shaw et al, 2005). We refer to a contact nucleation process as adhesion freezing when the position of the particle on the water surface enhances the ice nucleation efficiency compared with immersion freezing and discriminate it from collisional contact freezing, which assumes an enhancement due to the collision of the particle with the droplet (Nagare et al, 2016).…”
Section: Modes Of Heterogeneous Ice Nucleationmentioning
confidence: 99%
“…2C, Inset demonstrates that at various cooling rates, the ice nucleation temperature on the surfaces fully covered with IBFs remains higher than that on the GOPTS surface. For supercooled liquid water, ice nucleation of a droplet initiates at the most active site, and then ice grows spontaneously (29). Thus, to achieve lower ice nucleation temperature, it is required to sufficiently minimize the amount of nucleation active sites in contact with liquid water.…”
Section: Significancementioning
confidence: 99%